SN-Donor Methylthioanilines and Copper(II) Complexes: Synthesis, Spectral Properties, and In Vitro Antimicrobial Activity. (3rd March 2019) - Olalekan, Temitope E.; Ogunlaja, Adeniyi S.; Watkins, Gareth M.
Abstract : Methylthioanilines, a series of sulfur-nitrogen donor ligands substituted with OCH3, CH3, Cl, and Br, and their copper(II) complexes have been synthesized and characterized by 1 H and 13 C NMR, elemental analysis, FTIR, UV-Vis and EPR spectra, molar conductance, and magnetic susceptibility measurements. The NMR spectra of the ligands revealed that the para / ortho protons and para carbon were sensitive to the electronic effect of substituents. The CHNS analysis presented CuLCl2 (L = OCH3, CH3, Cl) and CuL2 Cl2 (L = Br) stoichiometries for the copper complexes. FTIR spectra showed that the bidentate ligands were coordinated to the copper ion through their nitrogen and sulfur atoms. The electronic spectra have suggested square planar and octahedral geometries for these complexes. The EPR spectra demonstrated that the solid state copper(II) complexes possess d x 2 – y 2 orbital ground state and g ∥ > g ⊥ > 2.0023 in a tetragonal environment. The compounds were evaluated for in vitro antimicrobial activity against S. aureus, B. subtilis, E. coli, and C. albicans . The copper complexes showed higher activity than the parent ligands against S. aureus and B. subtilis ; the electron-donating OCH3 and CH3 derivatives were more active than the withdrawing Br- and Cl-substituted compounds.